The nature and effects of inkind-guarrantee in the Iranian, Jordanian and Egyptian Law - Reza Hossein Gandamkar (مطالعات تطبیقی حقوق کشورهای اسلامی)
Objective guarantees are one of the important guarantees for fulfilling obligations in legal systems. Sometimes the guarantee is personal, and a person undertakes to pay the debtor's debt, and sometimes it is concrete, in such a way that a certain property becomes a guarantee for the payment of the debt. In personal deeds, due to factors such as default and bankruptcy of the guarantor, the right of the creditor is at risk. One of the reliable legal ways to guarantee the creditor's rights is to use concrete collateral. A surety bond or a surety bond is one of these sure methods. According to that, the guarantor, with the consent of the creditor, while assuming the debt, makes the payment of the debt from the property that belongs to him. In fact, there is a kind of private imprisonment for this property. In Iranian law, despite the guarantee contract and relatively detailed regulations, there are no regulations regarding the subject of the article, and the legal writers have not adequately covered all aspects of the subject.In the laws of Islamic countries, including Jordan, Egypt, this issue has been raised under the title of objective guarantee, and various debates have been raised regarding it. Considering the importance and applicability of the subject, this article has been dealt with in a comparative manner. The main question of this research is whether this type of legal institution is acceptable in Iran's legal system, and if the answer is yes, what are its nature and effects? In response to this question, with analytical and descriptive methods, we came to the conclusion that the nature of this contract is a combination of guarantee and mortgage, and its main and direct effects in the relationship between the guarantor and the creditor are the possibility of recourse by the creditor and the guarantor's obligation to pay the debtor's debt from the specified property. By paying the debt from the aforementioned property, the guarantor can refer to the debtor. When facing the creditor, the guarantor can refer to objections related to religion and what is not personal.